1998
DOI: 10.1038/sj.bjp.0701785
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin receptors mediating contraction of rat and human pulmonary resistance arteries: effect of chronic hypoxia in the rat

Abstract: 1 We examined the endothelin (ET) receptors mediating contractions to ET-1, ET-3 and sarafotoxin S6c (SX6c) in rat pulmonary resistance arteries by use of peptide and non-peptide ET receptor antagonists. Changes induced by pulmonary hypertension were examined in the chronically hypoxic rat. The e ect of the mixed ET A /ET B receptor antagonist SB 209670 on endothelin-mediated contraction was also examined in human pulmonary resistance arteries. 2 In rat vessels, the order of potency for the endothelin agonists… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 37 publications
2
57
1
Order By: Relevance
“…There is experimental evidence that both ET A and ET B receptors modulate ET-1 responses in small muscular pulmonary arteries of humans, and that combining blockade of both receptor subtypes can block ET-1-induced pulmonary vasoconstriction. 25 Nevertheless, ET A selective antagonists have been effective in improving cardiovascular function and structure in numerous experimental animal studies, suggesting therapeutic efficacy with ET A receptor blockade alone. It has been demonstrated that ET B receptor blockade alone impairs pulmonary clearance of ET-1 and reduces nitric oxide-mediated vasodilation.…”
Section: Et Receptor Blockade For Cardiovascular Diseasementioning
confidence: 99%
“…There is experimental evidence that both ET A and ET B receptors modulate ET-1 responses in small muscular pulmonary arteries of humans, and that combining blockade of both receptor subtypes can block ET-1-induced pulmonary vasoconstriction. 25 Nevertheless, ET A selective antagonists have been effective in improving cardiovascular function and structure in numerous experimental animal studies, suggesting therapeutic efficacy with ET A receptor blockade alone. It has been demonstrated that ET B receptor blockade alone impairs pulmonary clearance of ET-1 and reduces nitric oxide-mediated vasodilation.…”
Section: Et Receptor Blockade For Cardiovascular Diseasementioning
confidence: 99%
“…12 In contrast, ET B receptors are present on both ECs and VSMCs in the rat and human pulmonary circulations. 13 Stimulation of endothelial ET B receptors causes vasodilation through release of NO and prostacyclin and also functions to remove ET-1 from the circulation. 14,15 Stimulation of ET B receptors on smooth muscle causes vasoconstriction in the rat lung.…”
mentioning
confidence: 99%
“…observation is consistent with the previous pharmacological studies utilizing small pulmonary arteries isolated from normal rats in which ETB receptor agonist is more potent to induce vasoconstriction than ET-1. ETA receptor antagonist had little effects on the ET-1-induced vasoconstriction [1,27]. Conversely, ETA receptor antagonists prevented ET-1 induced vasoconstriction utilizing the main rat pulmonary artery [28].…”
Section: Discussionmentioning
confidence: 99%